Antimicrobial and Mosquito Repellent Finish on Cotton Fabric Using Coleus Aromaticus Leaf Extract. Issue 12 (2nd December 2022) - Boominathan, Senthilkumar; Magesh, G.; Balakrishnan, Senthilkumar
ABSTRACT: In this study, the combined antimicrobial and mosquito repellency treatment on woven cotton fabric using microencapsulated Coleus aromaticus was optimized through Box Behnken experimental design tool. The methanol-based solvent extraction was carried out for the preparation of crude extract from coleus aromaticus. The microcapsules were prepared using Gum acacia as shell material and Coleus aromaticus leaf extract as core material. These capsules were applied over the Cotton fabric through pad-batch method. Three process parameters have been taken for optimization, such as microcapsule concentration (gpl), concentration of BTCA, and curing temperature. The treated fabrics were subjected to antimicrobial activity and mosquito repellency characterization. Subsequent to this, polynomial equation was developed for both antimicrobial activities, as well as mosquito repellency behavior. Through RSM analysis, the influences of each process variables on the response were analyzed. The optimum process parameters are such as the concentration of microcapsule 40gpl, the concentration of BTCA 67.5 gpl, and the curing temperature was 116°C. The combined desirability coefficient was found as 0.792. Further to this, SEM and FTIR studies were executed for the confirmation of microencapsulated treatment effectiveness.